Knowledge, attitude, and behavior regarding breast cancer screening among women referring to health centers of Yazd city - Seyyed Mostafa Shiryazdi; Saeed Kargar; Ali Reza Farahbod; Hosein Neamatzadeh; Mohaddeseh Aboueian-Jahromi (Shahid Sadoughi University of Medical Sciences, 2014)
Abstract: Background: Early detection of breast cancer has a direct relationship with women's knowledge about breast cancer and its screening methods. Knowledge, attitude, and behavior of women in Yazd haven't yet surveyed, however breast cancer is one of health institute's priorities. The objective of this study is to survey the knowledge, attitude, and behavior regarding breast cancer screening among women referring to health centers of Yazd city and its relationship with demographic variables. Material and Methods: This cross-sectional descriptive study was conducted on 438 women referring to health centers of Yazd city in 2010 by using cluster sampling. For collecting data, a standard questionnaire contains demographic characteristics, determination of knowledge; attitude; and behavior, reasons for not practicing and practicing breast self examination, and informing sources for breast cancer and screening techniques is designed and rated. The data are analyzed by statistical tests of SPSS software. Results: The knowledge of breast cancer screening techniques is about moderate to poor 380(86.8%) people and has a significant relationship with educational level and age. Attitude is about moderate 310(70.8%) people and has a significant relationship with age and job. Behavior is poor 288(65.8%) people and has a significant relationship with all variables other than familial history. The main reason for not practicing breast self examination is reported "not being aware of correct breast self examination practice" 184(59.4%) people. The most important source for informing is television. Conclusion: The Knowledge, attitude, and practice of women referring to health centers of Yazd are consistent with most studies.